2013
DOI: 10.4236/ajps.2013.412a3017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rice Nursery Nutrient Management, Seeding Density and Seedling Age on Yield and Yield Attributes

Abstract: To help farmers in the mid hills of Nepal improve their crop management and rice yields, we conducted a study testing different nursery management options and their effect on grain yield and yield components under rainfed conditions. The experiment was conducted in a farmer's field during the cropping season 2009 and 2010 at Sundarbazar, Lamjung, Nepal, using a 3-factor factorial RCB design with 3 replications. The three management factors tested were 1) fertilizer management in the nursery, 2) seeding density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
23
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 10 publications
9
23
2
Order By: Relevance
“…Similarly, Amin and Haque (2009) reported that 35-d-old seedlings were better than younger (15-and 25-d-old) or older (45-d-old) ones. The better performance of older seedlings (35-45-d-old as compared with 25-30-d-old) was also reported by Channabasappa et al (1998), Alam et al (2002), Ella and Ismail (2006), Adhikari et al (2013), Sumon et al (2013), andBhowmick et al (2014) in less favorable conditions. Older seedlings had higher dry biomass and carbohydrate storage at transplanting.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Similarly, Amin and Haque (2009) reported that 35-d-old seedlings were better than younger (15-and 25-d-old) or older (45-d-old) ones. The better performance of older seedlings (35-45-d-old as compared with 25-30-d-old) was also reported by Channabasappa et al (1998), Alam et al (2002), Ella and Ismail (2006), Adhikari et al (2013), Sumon et al (2013), andBhowmick et al (2014) in less favorable conditions. Older seedlings had higher dry biomass and carbohydrate storage at transplanting.…”
Section: Discussionsupporting
confidence: 73%
“…Mustari et al (2013) found that seedlings from nurseries with low seeding density (25 g m −2 versus 40 g m −2 ) were more vigorous and had a yield advantage ranging from 29% to 141% for different varieties and submergence conditions, with greater response in tall, submergence-intolerant varieties such as Mahsuri. Better stress tolerance and higher yields due to healthy and vigorous seedlings were also reported by TeKrony and Egli (1991), Ella and Ismail (2006), Singh et al (2012), and Adhikari et al (2013).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Furthermore, and importantly, the effects of low nutrient supply in the nursery were not reversed by applying higher rates of fertilizer after transplanting or by transplanting older seedlings. Similarly, Shalaby et al [11], Rajagopalan and Krishnarajan [12] and Panda et al [13] found that nutrient application to nurseries improved rice grain yield while Adhikari et al [7] found no effect of nursery N fertiliser application on post-transplanting growth or yield of rice on a moderately fertile loamy soil in the mid-hills of Nepal.…”
Section: Discussionmentioning
confidence: 99%
“…Seedlings of advanced age may behave differently in their response to nursery fertilizer application and to post-transplanting stress. Adhikari et al reported that transplanting 40-day-old rice seedlings increased rice yield and effective tiller number in the monsoon season compared to 20-day-old rice seedlings on a loamy, moderately fertile soil in Nepal [7]. By contrast, a number of recent studies, spurred by the interest in the system for rice intensification (SRI), have found increased post-transplanting rice yield from seedlings as young as 10 days compared to those 20 -40 days old [8].…”
Section: Introductionmentioning
confidence: 99%